Research on Permanent Magnet-Type Super-Low-Frequency Mechanical Antenna Communication - Xiaoyu Wang; Wenhou Zhang; Xin Zhou; Zhenxin Cao; Xin Quan (International Journal of Antennas and Propagation)
In the super-low-frequency (30∼300 Hz) band communication, the traditional antenna covers a large area and has low radiation efficiency. The excitation of electromagnetic waves by the mechanical motion of permanent magnets enables miniaturized technology for super-low-frequency communication. For this miniaturization technique, this paper proposes a super-low-frequency communication architecture framework. Theoretical analysis and experimental verification of each unit module in the structural framework are carried out to achieve high-quality communication. For the radiation unit, permanent magnet parameters and communication distances are introduced to establish a rotating permanent magnet radiation power analysis model and to study the radiation characteristics of rotating permanent magnets. For the receiver unit, a sensitivity normalization characterization method based on the ratio of the coil thermal noise voltage to the induced voltage is proposed. Based on the sensitivity analysis model, a square coil was developed that meets the communication requirements of a mechanical antenna and an experimental platform was built. Experiments are conducted on the factors affecting radiated power and coil sensitivity, and 2FSK signal modulation communication experiments are conducted to verify the feasibility of the communication structure framework. The volume of the mechanical antenna permanent magnets in the experiment is all below 10 cm3, and the operating frequency is continuously adjustable from 0 to 250 Hz. The experimental results show that the near-field radiated power of a rotating permanent magnet is proportional to square of the volume of the rotating permanent magnet; the sensitivity of the coil is proportional to the number of turns and the area of the coil. By controlling the speed in real time, you can control the frequency of the signal and modulate it.